CAA2014 21st century archaeology : concepts, methods and tools : proceedings of the 42nd Annual Conference on Computer Applications and Quantitative Methods in Archaeology - Giligny, François,; Djindjian, François,; Costa, L.,; Moscati, P.,; Robert, S., (Archaeopress, 2015)
This volume brings together a selection of papers proposed for the Proceedings of the 42nd Computer Applications and Quantitative Methods in Archaeology conference (CAA), hosted at Paris 1 Panthǒn-Sorbonne University from 22nd to 25th April 2014. The program was divided into different themes and this structure has been maintained in the arrangement of articles in the various chapters of this book.